Analisis Tentang Perspektif Guru Sebagai Pendidik Dalam Tinjauan Al Qur’an - Windi Alya Ramadhani; Nina Novita; Amanda Putri Sari; Shafa Fakhlefi; Wismanto Wismanto (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
In the world of education, the role of teachers is very important in the teaching and learning process. As an educator, the teacher functions as a normative reference to foster self-awareness. This is one of the five educational factors, and its existence determines the course of the educational process. The aim of this research is to gain a clear understanding of the role of teachers as educators, to gain an understanding of the typology of teachers with all the requirements, characteristics and tasks, as well as an understanding of the multiple roles of teachers. This research uses qualitative methods with a library research approach. The main data source comes from information obtained through the latest books, magazines and/or journals related to this research theme. The results of this research show that teachers often play multiple roles to achieve learning goals. Sometimes the teacher plays the role of murabbi, sometimes as a Muslim, sometimes as a muaddib, sometimes as a mudarris to a murshid and various other roles which in fact, if further developed in other research, it will be found that there are many roles that can be carried out by a professional teacher.